Complexation of NpV Ions with 1, 10‐Phenanthroline‐2, 9‐dicarboxylic Acid: Spectrophotometric and Microcalorimetric Studies. Issue 32 (6th October 2014) - Yang, Yanqiu; Zhang, Zhicheng; Luo, Shunzhong; Rao, Linfeng
Abstract: The complexation of Np V ions with a tetradentate ligand with oxygen and nitrogen donors, 1, 10‐phenanthroline‐2, 9‐dicarboxylic acid (denoted as H2 L), was studied in aqueous solutions by spectrophotometric and calorimetric methods. Np V ions form a very strong 1:1 complex, NpO2 L –, with the stability constant log β = 11.73 ± 0.02 in 0.1M NaClO4 at 25 °C. It is a much stronger complex than those of Np V ions with related ligands such as picolinic acid or dipicolinic acid, as the higher denticity of 1, 10‐phenanthroline‐2, 9‐dicarboxylic acid results in a larger entropic effect on the complexation. It is expected that the amide derivatives of 1, 10‐phenanthroline‐2, 9‐dicarboxylic acid would be excellent extractants in the separation of Np V ions, which are problematic in actinide separation processes owing to their very low extractability by many extractants. Abstract : The large conjugated phenanthroline moiety in 1, 10‐phenanthroline‐2, 9‐dicarboxylic acid provides a planar configuration in which the four donor atoms are "preorganized" into optimal positions to coordinate to the equatorial plane of NpO2 + ions to form a very strong tetradentate complex.